N-Doped Carbon Boosted the Formation of Few-Layered MoS2 for High-Performance Lithium and Sodium Storage - Li, Junfeng; Zhou, Xianzi; Lu, Kai; Ma, Chao; Li, Liang; Wang, Haibao; Han, Xuejiao; Sun, Hengchao; Sun, Shinbin (Frontiers in Materials, 2021)
Molybdenum sulfide (MoS2) has become a potential anode of lithium-ion batteries (LIBs) and sodium-ion batteries (SIBs) due to its high theoretical capacity and low cost. However, the volume expansion, poor electrical conductivity and dissolution of polysulfides in the electrolyte during the cycling process severely limited its applications. Herein, few-layered MoS2@N-doped carbon (F-MoS2@NC) was synthesized through a facile solvothermal and annealing process. It was found that the addition of N-doped carbon precursor could significantly promote the formation of few-layered MoS2 and improve the performances of lithium and sodium storage. A high reversible capacity of 482.6 mAh g-1 at a high current density of 2000 mA g-1 could be obtained for LIBs. When used as anode material for SIBs, F-MoS2@NC hybrids could maintain a reversible capacity of 171 mAh g-1 at a high current density of 1000 mA g-1 after 600 cycles. This work should provide new insights into carbon hybrid anode materials for both LIBs and SIBs.